Organizations Driving Positive Social Change - Stephan, Ute; Patterson, Malcolm; Kelly, Ciara; Mair, Johanna (Journal of Management, 2016)
Academic and practitioner interest in how market-based organizations can drive positive social change (PSC) is steadily growing. This paper helps to recast how organizations relate to society. It integrates research on projects stimulating PSC—the transformational processes to advance societal well-being—that is fragmented across different streams of research in management and related disciplines. Focusing on the mechanisms at play in how organizations and their projects affect change in targets outside of organizational boundaries, we (1) clarify the nature of PSC as a process, (2) develop an integrative framework that specifies two distinct PSC strategies, (3) take stock of and offer a categorization scheme for change mechanisms and enabling organizational practices, and (4) outline opportunities for future research. Our conceptual framework differentiates between surface- and deep-level PSC strategies understood as distinct combinations of change mechanisms and enabling organizational practices. These strategies differ in the nature and speed of transformation experienced by the targets of change projects and the resulting quality (pervasiveness and durability), timing, and reach of social impact. Our findings provide a solid base for integrating and advancing knowledge across the largely disparate streams of management research on corporate social responsibility, social entrepreneurship, and base of the pyramid and open up important new avenues for future research on organizing for PSC and on unpacking PSC processes.